Baseline MRI findings as predictors of hypopituitarism in patients with non-functioning pituitary adenomas. Issue 11 (8th November 2021) - Al Argan, Reem; Ramadhan, Abdulaziz; Agnihotram, Ramanakumar V; Chankowsky, Jeffrey; Rivera, Juan
Abstract : Hypopituitarism tends to occur in large pituitary adenomas. However, similar tumors could present with strikingly different hormonal deficiencies. In this study, we looked at MRI characteristics in non-functioning pituitary adenomas (NFPA), which could predict secondary adrenal insufficiency (SAI) and central hypothyroidism (CHT). We reviewed the files of patients with NFPA attending our clinic. Tumor size, invasiveness, MR-signal intensity, and gadolinium enhancement in preoperative MRI were recorded along with documented presurgical hypopituitarism profile. Logistic regression was used to predict SAI, CHT, or both (SAI/CHT) based on MRI and demographic parameters. Receiver operating characteristic curves were used to determine their diagnostic utility. One hundred twenty-one patients were included in the study. Older age ( P = 0.021), male sex ( P = 0.043), stalk deviation ( P < 0.0001), contrast enhancement ( P = 0.029), and optic chiasma compression ( P = 0.012) were associated with SAI/CHT. Adenoma vertical height, largest diameter, and estimated volume were also strongly associated with SAI/CHT ( P < 0.0001). These associations remained significant in a multivariate analysis. No tumor smaller than 12 mm in vertical height, 17 mm in largest diameter, or 0.9 cm 3 in volume was associated with SAI/CHT. At cut-off ≥18 mm for vertical height, ≥23 mm for largest diameter, and ≥3.2 cm 3 the sensitivity was around 90–92% for detecting SAI/CHT. Only vertical height was significantly associated with any one or more pituitary hormonal deficit ( P = 0.001). In conclusion, adenoma size, independent of the measurement used, remains the best predictor of SAI/CHT in NFPA. Dynamic testing to rule out SAI is probably indicated in adenomas larger than 18 mm vertical height, 23 mm largest diameter and 3.2 cm 3 adenoma volume.